Curcuma suraponii sp. nov. (Zingiberaceae), a new species of Curcuma subgen. Curcuma from Thailand - THAWATPHONG BOONMA (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Boonma T. 2023. Curcuma suraponii sp. nov. (Zingiberaceae), a new species of Curcuma subgen. Curcuma from Thailand. Biodiversitas 24: 4885-4895. A new species, Curcuma suraponii Boonma sp. nov. has been collected in Tak Province, Northern Thailand during an exploration of Zingiberaceae diversity. This species belongs to the family Zingiberaceae and the genus Curcuma subgen. Curcuma. The plant materials were collected from their natural habitats and measurements were recorded from both living and preserved specimens. This species bears resemblance to Curcuma rubrobracteata Škorni?ková, Sabu & Prasanth, but differs in certain morphological characteristics and does not match any existing species. Therefore, the author described it as a new species to science under the name Curcuma suraponii Boonma. The description includes detailed information on its morphological characteristics, supported by illustrations, and provides the vernacular name, ecology, phenology, traditional utilization, conservation status, distribution map, and a comparative table to highlight its differences with allied species. Additionally, a revised key of 29 species within the Curcuma subgen. Curcuma in Thailand is also presented.